1998
DOI: 10.1074/jbc.273.1.235
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Residues and Motifs in the NixA Protein ofHelicobacter pylori Are Critical for the High Affinity Transport of Nickel Ions

Abstract: NixA, the high affinity nickel transport protein of Helicobacter pylori, imports Ni 2؉ ions across the cytoplasmic membrane for insertion into the active site of the urease metalloenzyme, which is essential for colonization of the gastric mucosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
79
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 29 publications
(32 reference statements)
2
79
0
Order By: Relevance
“…Members of this family usually have eight trans-membrane domains (Saier et al 1999) and topology studies using lacZ and phoA gene fusions revealed this was indeed the case for H. pylori NixA (Fulkerson and Mobley 2000). Conserved Asp, Glu and His residues are located in the transmembrane domains and appear to be critical for nickel transport (Fulkerson et al 1998); in addition, two essential domains have been characterized within helix II (GXXHAXDADH) and helix III (GX2FXXGHSSVV) of NixA (Fulkerson and Mobley 2000). Furthermore, other amino acids, including some with low in vitro affinity to nickel, have been shown to be also important for the function of NixA (Wolfram and Bauerfeind 2002).…”
Section: Nixa the Nickel-specific Permeasementioning
confidence: 90%
“…Members of this family usually have eight trans-membrane domains (Saier et al 1999) and topology studies using lacZ and phoA gene fusions revealed this was indeed the case for H. pylori NixA (Fulkerson and Mobley 2000). Conserved Asp, Glu and His residues are located in the transmembrane domains and appear to be critical for nickel transport (Fulkerson et al 1998); in addition, two essential domains have been characterized within helix II (GXXHAXDADH) and helix III (GX2FXXGHSSVV) of NixA (Fulkerson and Mobley 2000). Furthermore, other amino acids, including some with low in vitro affinity to nickel, have been shown to be also important for the function of NixA (Wolfram and Bauerfeind 2002).…”
Section: Nixa the Nickel-specific Permeasementioning
confidence: 90%
“…Further examination of this alignment identified 12 conserved Asp, Glu, and His residues which were postulated to be involved in Ni 2ϩ transport (20). These included the sequence motif GX 2 HAXDADH, which was conserved among NixA and its homologs, as well as in the NikC component of the nonhomologous Nik ATP-binding cassette transporter of Escherichia coli (20,50).…”
mentioning
confidence: 99%
“…These included the sequence motif GX 2 HAXDADH, which was conserved among NixA and its homologs, as well as in the NikC component of the nonhomologous Nik ATP-binding cassette transporter of Escherichia coli (20,50). The motif GX 2 FX 2 GHSSVV, which is also shared among the four single-component Ni 2ϩ transporters, is also present as a slight variant in the NhlF Ni 2ϩ -sensitive Co 2ϩ transporter of Rhodococcus rhodochrous (20,27,50). Both sequence motifs were also predicted to be in the NicT protein, recently identified as encoded in the genome of Mycobacterium tuberculosis (10), as well as in additional putative homologs identified in the genome sequences of Salmonella typhi (4) and Schizosaccharomyces pombe (29).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 These two proteins share a topology with eight transmembrane domains, 11,12 and two conserved histidine-rich motifs critical for metal uptake (GX 2 HX 4 DH and GX 2 FX 2 GH). 11,13 The UreH group includes Ni-specific permeases whose corresponding genes are associated with gene clusters for urease or Ni-superoxide dismutase in the genome of Bacillus and also in several proteobacteria and cyanobacteria. 5,14 Finally, members of the HupE/UreJ family are widespread among bacteria, and are usually encoded within hydrogenase or urease gene clusters.…”
Section: Introductionmentioning
confidence: 99%